Business Process Life Cycle Affects Company Financial Performance: Micro, Small, and Medium Business Enterprises During The Covid-19 Period - Widarti, Widarti; Desfitrina, Desfitrina; Zulfadhli, Zulfadhli (International Journal of Economics and Financial Issues, 2020)
The business process life cycle is a collection of structured work activities that are interconnected to solve a problem that results in an output (product / output) or service that achieves goals and supports the achievement of strategic goals and objectives of an organization’s financial performance. Business processes aim to achieve financial performance that is effective, efficient and increases the productivity of an organization. The life cycle of micro, small and medium enterprises aims to survive post-Covid-19 in order to increase the productivity performance of the organization’s financial performance. To achieve this goal, an organization needs a good business process to support the organization’s financial performance and business ventures in designing activities to produce new products in order to develop management techniques so that they can survive the midst of the global Covid-19 crisis. The product life cycle that can identify opportunities for environmental improvement is an important part of an organization that aims to minimize total costs, low prices and production results, improve the financial performance of micro, small, and medium business processes. Techniques in producing using financial and non-financial information, to improve the company’s financial performance, and to contribute to the sustainability of business processes aim to provide physical information on material and energy use, as well as monetary information on costs, revenues and savings related to the company’s financial performance. This research was carried out on micro, small and medium enterprises in Indonesia. This research method is descriptive and verification methods, the analysis tool is structural equation modeling (SEM, Lisrel). The results showed that the business process life cycle had an effect on the financial performance of the Covid-19 small, and medium enterprises business companies. Keywork: Business Process Life Cycle, Corporate Financial Performance. Micro, Small, And Medium Enterprises, Covid-19 Period JEL Classifications: E3, G2 DOI: https://doi.org/10.32479/ijefi.10516